Islamic Marketing Mix Home Sharing Strategy at Multi Level Marketing Natural Nusantara - Rinatul Jannah; Abdul Rokhim; Ahmadiono Ahmadiono (Jurnal Syntax Admiration, 2023)
Home sharing is a business meeting that is held in a simple place such as a home or stockist to explain business opportunities to others and convey information so that it is effective and provides many benefits in carrying out its activities by using Islamic Marketing Mix to be able to reach the target market in a Multi Level Marketing company Natural Nusantara which sells beauty, health, agriculture, animal husbandry and fishery products. The formulation of the problems in this research are 1) What is the strategy of Islamic Marketing Mix Home Sharing on Multi Level Marketing Natural Nusantara 2) What are the implications of the Islamic Marketing Mix Home Sharing strategy on sales turnover of Multi Level Marketing Natural Nusantara. The approach in this study is a descriptive qualitative method and is a field research by observing, interacting and direct observation based on the phenomena that occur to the research subjects. This research can be concluded 1) Home Sharing Natural Nusantara has benefits in carrying out its activities in accordance with the sharia marketing mix in Islamic marketing which includes product, price, place, promotion, people, process, physical evidence, promise, patience, and customer centrism. 2) The implications of the Islamic Marketing Mix strategy on sales turnover have a direct impact namely sales increase after Home Sharing activities are carried out.